The Normative Emergence of Death in the Organization of American States’ Responses to COVID-19: towards a Regional Governance of Death - Marconi, Cláudia A.; Santos, Isabela Agostinelli Dos [UNESP]; Miranda, Rafael De Souza Nascimento (Pontifícia Universidade Católica do Rio de Janeiro, Instituto de Relações Internacionais, 2022)
The COVID-19 pandemic has been (re)creating new global geographies of death, which specifically impact the Global South and expose its continuum of vulnerabilities – unequally distributed in terms of race, gender, class, and so on. In the Americas, we can identify the emergence of a new regional governance of death, associated with a set of practical recommendations by the Organization of American States (OAS) constraining states’ policy responses to COVID-19 and installing a new global governance lexicon. Recommendations concerning the disposal of dead bodies, full respect for both collective and family grief, and indications of alternative ways to conduct funerals and memorial services, for instance, seem to evoke new multilateral responses, paving the way for a new governance model: one that centres death within regional policymaking. This points to a change in the treatment of death from a purely private to a politically infused issue. Theoretically, this article aims to bridge the gap between Death Studies and Global Governance literatures. Supported by Michel Foucault’s genealogical method, the goal is to critically reconceptualise the meanings and framings of death landscapes in the Americas, pointing us to the correlation of forces that enabled the normative emergence of death in the OAS in this particular historical moment.

A pandemia do COVID-19 vem (re)criando novas geografias globais da morte, que impactam especificamente o Sul Global e expõem seu continuum de vulnerabilidades – distribuídas desigualmente em termos de raça, gênero, classe e assim por diante. Nas Américas, podemos identificar o surgimento de uma nova governança regional da morte, associada a um conjunto de recomendações práticas da Organização dos Estados Americanos (OEA) restringindo as respostas políticas dos Estados à COVID-19 e instalando um novo léxico de governança global. As recomendações sobre o descarte de cadáveres, o pleno respeito ao luto coletivo e familiar e as indicações de formas alternativas de realizar funerais e velórios, por exemplo, parecem evocar novas respostas multilaterais, abrindo caminho para um novo modelo de governança: aquele que centra a morte na formulação de políticas regionais. Isso aponta para uma mudança no tratamento da morte de uma questão puramente privada para uma questão politicamente infundida. Teoricamente, este artigo visa preencher a lacuna entre os Estudos da Morte e as literaturas de Governança Global. Apoiado no método genealógico de Michel Foucault, o objetivo é reconceituar criticamente os significados e enquadramentos das paisagens da morte nas Américas, apontando para a correlação de forças que possibilitaram a emergência normativa da morte na OEA neste momento histórico particular.
A emergência normativa da morte nas respostas da Organização dos Estados Americanos à COVID-19: rumo a uma governança regional da morte
Keywords: OAS; regional governance; policy responses; deathscapes; COVID-19 crisis; OEA; governança regional; respostas políticas; paisagens de morte; crise de COVID-19